Understanding What Drives Crypto Tax Reporting in Indonesia: Knowledge and Demographic Factors - Suseno , Matthew Aryo; Oktavia (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2025)
This study examines the influence of tax knowledge related to digital transactions and demographic factors—measured by educational level and income level—on individual compliance in reporting cryptocurrency assets in Indonesia's Annual Tax Return. Data were collected through a structured questionnaire distributed to cryptocurrency investors on platforms such as Tokocrypto, Indodax, and Stockbit Crypto. The findings indicate that tax knowledge regarding digital transactions, educational level, and income level all positively and significantly impact cryptocurrency reporting compliance. These results suggest that improving taxpayers' understanding of digital tax regulations and strengthening demographic factors such as education and income can enhance compliance behaviour.